Electrical properties of molten CuCl-Cu2Se mixtures - Tahara S.; Ishida K.; Ohno S.; Okada T. (EPJ Web of Conferences, 2011)
The electrical conductivity, σ, and the thermoelectric power, S, have been measured for molten CuCl-Cu2Se mixtures as a function of composition and temperature. The electrical conductivity of their mixtures decreases rapidly with the addition of CuCl to liquid Cu2Se. The thermoelectric power of molten CuCl-Cu2Se mixtures shows a steady increase with increasing the composition of CuCl. The experimental results suggest that the dominant transport process in the molten CuCl-Cu2Se mixtures changes from electronic to ionic conduction. The composition dependence of σ and S was analyzed by using the fundamental equation of electrical current densities due to the electrons and the ions. According to this analysis, the conductivity gap increases gradually on the addition of CuCl to liquid Cu2Se and the conductivity gap is about 0.68 eV for molten (CuCl)0.3(Cu2Se)0.7 mixture.